Student Difficulties in English Language Pronunciation: A Qualitative Study of Tenth-Grade Students at Senior High School - Juleha Santrika; Emeliya Sukma Dara Damanik (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The object of this study is to investigates the student difficulties in pronunciation of student MAN 2 Model Medan. The research design used qualitative research with observation and interviews as data collection techniques, the participants in this study were tenth-grade students, namely Rara, Mutia, and Faika. The results showed that the students encountered various challenges, including difficulties in differentiating similar sounds for example live vs. leave, see vs. sea, incorrect use of stress and intonation, and lack of fluency caused by low confidence. These problems were influenced by first language interference, limited phonological awareness, and psychological barriers such as nervousness and fear of making mistakes. The study also found that pronunciation instruction was rarely prioritized in the classroom, as English lessons focused more on grammar and vocabulary. Although some students attempted to overcome their problems through independent practice, such as using YouTube, these efforts were not consistent. This research suggests that teachers should implement more student- centered approaches to teaching pronunciation. Regular practice, constructive feedback, and supportive learning environments are needed to help students build confidence, reduce anxiety, and improve their ability to communicate effectively in English.